The effect of financial risk on the earnings response in Thailand banks' stock - Soh, Wei Ni; Cheng, Fan Fah; Md Nassir, Annuar (EuroJournals Publishing, 2009)
Financial institutions are often treated differently from non-financial businesses since they provide a service as intermediaries of the capital and debt markets. This paper studies the commercial banks in Thailand, one of the Asia-Pacific countries, uses the concept from earnings response literatures and extended with the risk management measures to find out whether the estimated financial risks have incremental information content beyond earnings. Analysts discover that the earnings announcements played a role in influence the movement of the shares price when they were not anticipated. Using stock price data and bank's earnings announcements, some analysts discover that financial institutions' specific experiences and earnings announcements indeed affect the investor's trading decision on the banks stocks. This study, which uses the more accurate risk-adjusted returns and regression methodology, is about the financial risk effect on bank shares revaluation in a capital market in the region. This procedure discovers that Thailand investors look at the interest risk significantly in the earnings response valuation among the other financial risks variables. These findings suggest the relevant of the financial risk exposure in the Thailand banks using the latest data.